Root Vs route: the diaspora of cocos Malays and their dwelling culture - Hj Mohd Ariffin, Noor Aziah; Osri, Nurul Ain; Salleh, Nurul Hamiruddin (2017)
The paper explored the diaspora of the Cocos Malays within the bigger context of the Malay diaspora. The emphasis was on the unique anthropology and dwelling culture of the Cocos Malays in Cocos (Keeling) Island, Australia and the emigrated Cocos Malays in Sabah, Malaysia. Cocos Malays originated from Cocos (Keeling) Islands in the Indian Ocean, were initially British subjects but are Australians now. In the 1950s some of them emigrated to North Borneo (Sabah) and became Malaysians. The main idea behind this study was to investigate the history related to the settlement and dwelling culture of the Cocos Malays and to what extent do their heritage has on influencing the spatial organisations of their abodes. The ethnographic study utilising social research methods initiated with an inquiry about the Cocos Malay Islanders of Australia, but the passage of this study surprisingly took us back closer to home to Tawau in Sabah in East Malaysia. In Sabah, the Cocos Malays have created their settlements after being forced to emigrate, after the World War II from their Island in the 1950s. The study further deepens in tracing the evolution of their dwellings in Sabah to establish whether any historical or cultural influences they had on Cocos Island have impacted on the spatial organisations of their present houses. The findings indicated that not all of the existing dwelling culture on the Cocos Island was reflected in the present houses in Kampung Balung Cocos, of Sabah.